Immediate Response to Chemotherapy in an Adult Neuroblastoma Patient Presenting with Cord Compression - Nedal Bukhari; Bachar Harfouch; Majid Shallal Alotaibi; Hulayel Al-Harbi; Omar Chamdine (Case Reports in Neurological Medicine)
We report a case of a 31-year-old female patient with high-risk neuroblastoma (NBL) who presented with a history of static back pain and bilateral lower limb weakness for almost a month. Her primary tumor was located in the right paraspinal region, causing spinal cord compression (SCC). Chemotherapy was administered with an immediate clinical improvement noted after 24 hours of starting treatment. We herein report the efficacy of chemotherapy in an adult neuroblastoma (aNBL) patient presenting with spinal cord compression.